2022
DOI: 10.1007/s00586-022-07317-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between preoperative MRI findings and clinical improvement in patients included in the NORDSTEN spinal stenosis trial

Abstract: Purpose To investigate potential associations between preoperative MRI findings and patient reported outcome measures (PROMs) after surgery for lumbar spinal stenosis (LSS). Methods The NORDSTEN trial included 437 patients. We investigated the association between preoperative MRI findings such as morphological grade of stenosis (Schizas grade), quantitative grade of stenosis (dural sac cross-sectional area), disc degeneration (Pfirrmann score), facet join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The load did not affect the asymmetrical movement of the lumbar facet joints. Previous studies have shown that there is anatomical asymmetry in the lumbar zygapophyseal joints [26]. We believe that this anatomical asymmetry in the facet joints causes the asymmetrical movement patterns.…”
Section: Discussionmentioning
confidence: 70%
“…The load did not affect the asymmetrical movement of the lumbar facet joints. Previous studies have shown that there is anatomical asymmetry in the lumbar zygapophyseal joints [26]. We believe that this anatomical asymmetry in the facet joints causes the asymmetrical movement patterns.…”
Section: Discussionmentioning
confidence: 70%
“…Yamada et al using the JOA score and a VAS scale detected a higher prevalence of leg pain at rest in patients with lumbar foraminal stenosis compared with patients with predominantly central lumbar stenosis [33]. In a study by the NORDSTEN group, disk degeneration was found to be a predictor for less postoperative improvement in the ODI score [7]. The NORDSTEN group has formerly investigated potential associations between improvement in PROM and a range of MRI findings but could not detect any associations with clinical relevance when investigating Schizas score, DSCA, tropism, or amount of fatty infiltration of multifidus muscle [7].…”
Section: Discussionmentioning
confidence: 96%
“…The inter-and intra-observer agreement analysis regarding the preoperative MRI examinations is reported in a previous study [5]. The index level was defined as the narrowest lumbar level measured by dural sac cross-sectional area (DSCA) [7]. At the index level, the grade of foraminal stenosis was classified using sagittal T1-weighted images according to the classification system proposed by Lee et al [24].…”
Section: Radiological Variablesmentioning
confidence: 99%
See 2 more Smart Citations